The markers to delineate different phenotypes of macrophages related to metabolic disorders - Wei, Quxing; Deng, Yanyue; Yang, Qianqian; Zhan, Angyu; Wang, Lexun (Frontiers in Immunology, 2023)
Macrophages have a wide variety of roles in physiological and pathological conditions, rendering them promising diagnostic and therapeutic targets in diseases, especially metabolic disorders, which have attracted considerable attention in recent years. Owing to their heterogeneity and polarization, the phenotypes and functions of macrophages related to metabolic disorders are diverse and complicated. In the past three decades, the rapid progress of macrophage research has benefited from the emergence of specific molecular markers to delineate different phenotypes of macrophages and elucidate their role in metabolic disorders. In this review, we analyze the functions and applications of commonly used and novel markers of macrophages related to metabolic disorders, facilitating the better use of these macrophage markers in metabolic disorder research.